2021
DOI: 10.1126/sciadv.abj4273
|View full text |Cite
|
Sign up to set email alerts
|

Self-adaptive cardiac optogenetics device based on negative stretching-resistive strain sensor

Abstract: A closed-loop and self-adaptive cardiac optogenetics is realized by a negative stretching-resistive strain sensor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Reproduced with permission from ref. 74 Copyright 2021 AAAS. d , e Use of implantable optoelectronic devices for wireless optical stimulation ( d ) and neuromodulation ( e ).…”
Section: D Free-form Displaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproduced with permission from ref. 74 Copyright 2021 AAAS. d , e Use of implantable optoelectronic devices for wireless optical stimulation ( d ) and neuromodulation ( e ).…”
Section: D Free-form Displaysmentioning
confidence: 99%
“…Hong et al demonstrated an optogenetics therapy based on a closed-loop system consisting of a strain sensor array for heart rate monitoring, a processing circuit, and LEDs with self-adaptive light intensity control (Fig. 8c ) 74 . The strain sensor array wrapping around the heart could detect negative resistance variation over a wide strain range.…”
Section: D Free-form Displaysmentioning
confidence: 99%
“…Recently, flexible strain sensors have attracted much attention for their excellent performance in healthcare, − soft machines, − human–computer interfaces, − etc. These application scenarios put forward higher requirements for the design and manufacture of sensors, which should have high flexibility, stretchability, and excellent sensitivity to detect a wide range of strains, often depending on the substrate and sensitive material.…”
Section: Introductionmentioning
confidence: 99%
“…A myriad of strain sensors based on various sensing mechanisms including resistance [6], capacitance [7,8], piezoresistive [9], piezoelectric [10], and inductance [11,12] have been developed. To meet the growing demand for practical medical applications in variable harsh conditions, stretching-resistive strain sensors have been widely used due to their ease of manufacturing and integration, costeffectiveness, and scalability [13][14][15][16]. In general, resistive strain sensors turn strain to raising resistance as a result of gradual breaking of conductive path.…”
Section: Introductionmentioning
confidence: 99%
“…At present, crack-based resistive sensors have been widely fabricated to achieve high gauge factor (GF), which contributes to improvement of the sensitivity [17,18]. It is worth noting that resistor thermal noise, which is positively associated with resistance, also significantly influences the detection output [13,19]. Therefore, highly conductive materials such as metals, liquid metal, graphene, carbon nanotubes (CNTs), metallic nanoplates and nanowires (NWs) are often used to construct conductive materials [20][21][22].…”
Section: Introductionmentioning
confidence: 99%